Preventive treatment of tripdiolide ameliorates kidney injury in diabetic mice by modulating the Nrf2/NF-κB pathway - Yuan, Bo; Jia, Dan; Gao, Baoshan (Frontiers in Pharmacology, 2025)
IntroductionAlthough tripdiolide has demonstrated a protective role in lupus nephritis, its potential therapeutic and preventive effects on diabetic kidney injury remain inconclusive.MethodsIn this study, a diabetes mice model was used to evaluate the effect of preventive treatment of tripdiolide on the kidney. The study assessed diabetes related factors levels, while comparing kidney pathological changes, alterations in intestinal microbiota composition, oxidative stress and inflammation in kidneys, validating cytokine expression and protein pathway activation.ResultsThe experiment demonstrated that tripdiolide preventive treatment effectively suppressed the hyperglycemia and elevated hemoglobin level, attenuated the concentrations of creatinine and blood urea nitrogen, mitigated histopathological alterations in the kidney, and alleviated inflammatory cell infiltration. Tripdiolide regulated intestinal microbiota in diabetes mice and affected the abundance of Allobaculum, Dubosella, and Prevotella, and the differential metabolic pathways primarily revolve around ubiquinol biosynthesis and menaquinol biosynthesis. Tripdiolide treatment significantly attenuated renal oxidative stress and inflammation in diabetic mice, as evidenced by the upregulation of nuclear factor erythroid 2-related factor 2 (Nrf2), heme Oxygenase-1, and the downregulation of phosphorylated nuclear factor-κB (P-NF-κB), and NOD-like receptor protein 3. Experiments performed in RAW264.7 cells demonstrated the effect of tripdiolide.DiscussionTripdiolide may play a protective role in hyperglycemia induced kidney injury by changing the composition of intestinal microorganisms, regulating Nrf2/NF-κB pathway activation, and inhibiting oxidative stress and inflammatory reaction. This study contributes scientific evidence that can inform the development of preventive therapeutic approaches for diabetic nephropathy.